Draft Fifth Five Year Plan 1974-79 Union Territory of Laccadive, Minicoy and Amindivi Islands - Planning Commission (Planning Commission, 1974)
Ten inhabited and ten uninhabited coral islands scattered in the Arabian Sea, about 200 to 400 Kilometres off the Kerala coast, constitute the Union Territory of Laccadive, Minicoy and Amindivi islands. The Islands are identical in structure and formation rising not more than about 10 meters above the sea. There are shallow lagoons on the western side encircled by coral reefs, beyond which lies the deep sea.
Union Territory of Laccadive, Minicoy and Amindivi Islands